Planejamento tributário e insegurança jurídica: a linguagem do código versus a linguagem do CARF na operação casa e separa - Brasil, Eduardo Tadeu Francez (2012)
This study investigates the general and abstract Positive Law rules that allow and don t allow individuals to perform tax planning. It examines the Brazilian Federal Constitution, the Brazilian National Tax Code and the Brazilian Civil Code. It is used as theoretical premise the semiotic constructivism, with its theoretical tools: theory of the values; language selfreference, enunciation, enunciation-enunciated, enunciated-enunciated; legal system autopoiesis; incidence and application of the law; concept of law norms and description of the functioning of the constitutional tax system. In a second moment, the decisions of the Brazilian Board of Tax Appeals (CARF) are analysed about the merger and spin off operation model for the period 2004 to 2010, in order to identify a behavior pattern that makes the operations performed by individuals as being enforceable or not to the revenue service and there is also the subsumption by the Government. That is, where the general and abstract rules CARF bases its decisions and which provides meaning to the concepts it employs. The aim is to compare the general and abstract language, as a constructivism bias, to the concrete and individual language standards issued by CARF. It is concluded that there is a decoupling of the legal reality about the dialogue between the two groups of languages. It is said that the legal uncertainty stands opposed to its safety, because there is a creation of two antagonistic body language and the language of the concrete isn t compatible with the general and abstract norm belonging to the current system of Positive Law in Brazil